2020
DOI: 10.1016/j.physa.2019.123871
|View full text |Cite
|
Sign up to set email alerts
|

Super-statistical description of thermo-magnetic properties of a system of 2D GaAs quantum dots with gaussian confinement and Rashba spin–orbit interaction

Abstract: We examine the effect of non-equilibrium processes modeled by the introduction of a generalized Boltzmann factor on the thermal and magnetic properties of an array of two-dimensional GaAs quantum dots in the presence of an external uniform and constant magnetic field. The model consists of a single-electron subject to a confining Gaussian potential with a spin-orbit interaction in the Rashba approach. We compute the specific heat and the magnetic susceptibility within the formalism of χ 2 -superstatistics from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 121 publications
(128 reference statements)
0
13
0
Order By: Relevance
“…In our case, we are focused on Gamma distribution defined by Eq. (16): this choice is justified by the wide use of this distribution in the literature: as an example, we can cite the following: in blinking quantum dots, cosmic ray statistics, various scattering processes in particle physics [9], one-dimensional Dirac oscillator [7] and the thermo-magnetic properties of a system of 2D GaAs quantum dots [34]. Other recent applications of the superstatistics are briefly reviewed by Refs.…”
Section: Partition Function In Superstatisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, we are focused on Gamma distribution defined by Eq. (16): this choice is justified by the wide use of this distribution in the literature: as an example, we can cite the following: in blinking quantum dots, cosmic ray statistics, various scattering processes in particle physics [9], one-dimensional Dirac oscillator [7] and the thermo-magnetic properties of a system of 2D GaAs quantum dots [34]. Other recent applications of the superstatistics are briefly reviewed by Refs.…”
Section: Partition Function In Superstatisticsmentioning
confidence: 99%
“…In the recent paper of Castaño et al [34], the authors used the q-algorithm of the q-calculus formalism [22,23] to discuss thermo-magnetic properties of a system of 2D GaAs quantum dots. Here we can mention two remarks about this formalism:…”
Section: Generalized Statistical Mechanics For Superstatistical Systemsmentioning
confidence: 99%
“…As shown in previous works [9,21],admitting parallelism between SS and non-extensive thermodynamics has profound implications in the energy constraints to let invariant the Legendre structure (LS) behind a thermal treatment. Although the computation of quantum entanglement in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Super-statistics (SS), developed by Beck and Cohen, is an effective way to study the non-equilibrium processes based on the idea that the thermodynamics of a system that passes through several equilibrium thermodynamic states or is divided into subsystems, each in local equilibrium, can be approximated by postulating an average Boltzmann factor weighted with the density probability function of fluctuations [1][2][3]. It has been applied to many topics: turbulence models [4,5], cosmic rays [6], quantum cromodynamics [7,8], quantum dots [9,10], out-of-equilibrium Ising models [11], quantum field theory [12,13], among others [14][15][16][17]. Then, SS is a subject that deserves attention.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that the Legendre transform structure is an essential ingradient [12]. In contranst, it is rarely noted that the Legendre transform structure may be unneccesary in the unconventional statistics [13]. It was also shown that the Legendre transform structure is robust against the choice of entropy and the definition of mean value [12,14].…”
Section: Introductionmentioning
confidence: 99%